Differential role of nicotinamide adenine dinucleotide deficiency in acute and chronic kidney disease. Issue 1 (25th October 2020) - Faivre, Anna; Katsyuba, Elena; Verissimo, Thomas; Lindenmeyer, Maja; Rajaram, Renuga Devi; Naesens, Maarten; Heckenmeyer, Carolyn; Mottis, Adrienne; Feraille, Eric; Cippà, Pietro; Cohen, Clemens; Longchamp, Alban; et al.
Abstract: Background: Nicotinamide adenine dinucleotide (NAD + ) is a ubiquitous coenzyme involved in electron transport and a co-substrate for sirtuin function. NAD + deficiency has been demonstrated in the context of acute kidney injury (AKI). Methods: We studied the expression of key NAD + biosynthesis enzymes in kidney biopsies from human allograft patients and patients with chronic kidney disease (CKD) at different stages. We used ischaemia–reperfusion injury (IRI) and cisplatin injection to model AKI, urinary tract obstruction [unilateral ureteral obstruction (UUO)] and tubulointerstitial fibrosis induced by proteinuria to investigate CKD in mice. We assessed the effect of nicotinamide riboside (NR) supplementation on AKI and CKD in animal models. Results: RNA sequencing analysis of human kidney allograft biopsies during the reperfusion phase showed that the NAD + de novo synthesis is impaired in the immediate post-transplantation period, whereas the salvage pathway is stimulated. This decrease in de novo NAD + synthesis was confirmed in two mouse models of IRI where NR supplementation prevented plasma urea and creatinine elevation and tubular injury. In human biopsies from CKD patients, the NAD + de novo synthesis pathway was impaired according to CKD stage, with better preservation of the salvage pathway. Similar alterations in gene expression were observed in mice with UUO or chronic proteinuric glomerular disease. NR supplementation did not prevent CKD progression, in contrast to its efficacy in AKI. Conclusion: Impairment of NAD + synthesis is a hallmark of AKI and CKD. NR supplementation is beneficial in ischaemic AKI but not in CKD models.